1985
DOI: 10.1111/j.1528-1157.1985.tb05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electrophysiologic Evaluation of Peripheral Nerve Function in Chronic Phenytoin Therapy

Abstract: Analysis of covariance was employed to explore possible correlations among duration of phenytoin therapy, phenytoin and folate serum concentrations, and clinical and electrophysiologic findings in 32 patients receiving single phenytoin therapy. None of our patients volunteered peripheral nervous system complaints. On examination, 9 of 32 (28%) were found to have signs suggestive of neuropathy (absent knee and/or ankle jerks). Neither phenytoin serum concentration nor duration of phenytoin therapy was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In agreement with results of other reports (Encinosa, 1974; Taylor et al, 1985), patient age in our series appeared to influence the risk of polyneuropathy. Even though the adverse effect of AED treatment on the peripheral nerve persisted even after we controlled for age, the greater susceptibility of elderly people to develop peripheral neuropathy when treated with AEDs must be stressed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with results of other reports (Encinosa, 1974; Taylor et al, 1985), patient age in our series appeared to influence the risk of polyneuropathy. Even though the adverse effect of AED treatment on the peripheral nerve persisted even after we controlled for age, the greater susceptibility of elderly people to develop peripheral neuropathy when treated with AEDs must be stressed.…”
Section: Discussionsupporting
confidence: 93%
“…AED dosage and plasma level did not appear to affect the risk of polyneuropathy, as shown by our report and those of other investigators (De Castro et al, 1972;Swift et al, 1981;Taylor et al, 1985). However, our patients were receiving AEDs at standard daily dosages and low to middle plasma concentrations, in contrast to the patients reported by Lovelace and Horwitz (1968), 22% of whom were receiving PHT a500 mg daily, and those of Shorvon and Reynolds (1982), who reported that 66% of their patients with abnormal conduction values had been exposed previously to toxic PHT dosages.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The data on the effects of AEDs on the peripheral nervous system are controversial, partly owing to methodologic difficulties and to the lack of correlation between AED serum levels and electrophysiologic abnormalities (Geraldini et al, 1984;Taylor et al, 1985). This study emphasizes use of multimodal sensory EPs and quantitative spectral EEG in evaluation of pharmacologic effects within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy, demonstrated clinically and by electrophysiological studies, arise in about 30% of patients treated with PHT alone (45). The patients seldom complain of symptoms.…”
Section: Neuropathymentioning
confidence: 99%